Impact of Intrinsic and Extrinsic Gaming Elements on Online Purchase Intention - Wu, Xiaomei; Santana, Silvia (Frontiers in Psychology, 2022)
Gamification is a developing trend that can work on customers’ motivation and performance in online business area. Notwithstanding, it is still vigorously bantered as there is a continuous conversation inside the gamification local area whether individual gamification components may really debilitate or work on customers’ intrinsic motivation and extrinsic motivation as well as the effect on the consumer’s perceived enjoyment and purchase intention. The paper uses questionnaire survey as the research method. Total of 310 questionnaires were distributed and after the calculation and data screening, it shows that 302 sets are valid data. The data analysis of this study was calculated by using SPSS and Smart-PLS. The findings of this study shows that intrinsic and extrinsic gaming elements affecting the consumers’ purchase intention in gamification. It shows extrinsic gaming elements such as badges, challenges, points, and feedback are affecting customers’ perceived enjoyment. Furthermore, intrinsic gaming elements such as avatars, leaderboard, levels, and privacy control are affecting customers’ perceived enjoyment. It also shows that perceived enjoyment positively affects purchase intention and mediates the relationship between intrinsic and extrinsic gaming elements and purchase intention. Additionally, it shows that promotion focus negatively moderates the relationship of intrinsic elements and perceived enjoyment. This paper presents a new research model to explore the effect of extrinsic and intrinsic elements in gamification on purchase intention. The results of this research may help the game designers to identify the right design features for the right customers, which has important practical implications for online business development.